Occasionally Binding Constraints in the New Keynesian Model - Mendes, D. A.; Mendes, V. (ICDEA 2021, 2021)
Our main goal is to analyze a standard macroeconomic model with occasionally binding constraints (OBCs) in this paper. This type of problem is quite ubiquitous in macroe- conomics but is usually ignored for high computational demands. For example, we can nd OBCs in models with a zero lower bound constraint on interest rates, in models with occasionally binding collateral constraints, downward nominal wage rigidities, irreversible investment, irreversible natural resources, or discrete decision making in Markov decision processes. In particular, we will focus on discussing the New Keynesian Model with a typical Taylor Rule on the nominal short-term interest rate. In this framework, we can consider two dierent states (a "normal" state and the "Zero Lower Bound" on interest rates), modeled according to a Markov process. The solution is obtained by the method of time iteration and follows the approaches recently presented by Sunakawa and Hirose (2019) and Rendahl (2017).